Stones in Motion: Cost units to understand flint procurement strategies during the Upper Palaeolithic in the south-western Pyrenees using GIS. (2016) - Prieto, Alejandro; García-Rojas, Maite; Sánchez, Aitor; Calvo, Aitor; Domínguez-Ballesteros, Eder; Ordoño, Javier; García-Collado, Maite Iris
No abstract available